Eikenella corrodens Phase Variation Involves a Posttranslational Event in Pilus Formation - Villar, Maria T. (American Society for Microbiology, 1999)
The human pathogen Eikenella corrodens synthesizes type IV pili and exhibits a phase variation involving the irreversible transition from piliated to nonpiliated variants. On solid medium, piliated variants form small (S-phase), corroding colonies whereas nonpiliated variants form large (L-phase), noncorroding colonies. We are studying the molecular basis of this phase variation in the clinical isolate E. corrodens VA1. A genomic fragment encoding the major type IV pilin was cloned from the S-phase variant of strain VA1. Sequence analysis of the fragment revealed four tandemly arranged potential open reading frames (ORFs), designated pilA1, pilA2, pilB, and hagA. Both pilA1 and pilA2 predict a type IV pilin. The protein predicted by pilB shares sequence identity with the Dichelobacter nodosus FimB fimbrial assembly protein. The protein predicted by hagA resembles a hemagglutinin. The region containing these four ORFs was designated the pilA locus. DNA hybridization and sequence analysis showed that the pilA locus of an L-phase variant of strain VA1 was identical to that of the S-phase variant. An abundant pilA1 transcript initiating upstream of pilA1 and terminating at a predicted hairpin structure between pilA1 and pilA2 was detected by several assays, as was a less abundant read-through transcript encompassing pilA1, pilA2, and pilB. Transcription from the pilA locus was nearly indistinguishable between S- and L-phase variants. Electron microscopy and immunochemical analysis showed that S-phase variants synthesize, export, and assemble pilin into pili. In contrast, L-phase variants synthesize pilin but do not export and assemble it into pili. These data suggest that a posttranslational event, possibly involving an alteration in pilin export and assembly, is responsible for phase variation in E. corrodens.